Comparison of Intense Pulsed Light With Nonablative Fractional Laser and Picosecond Alexandrite Laser With Diffractive Lens Array for Noninvasive Facial Rejuvenation - Zhu, Jiafang; Chang, Rui; Han, Yue; Xi, Qianwen; Jiang, Shutian; Shang, Ying; Lyu, Dongze; Yu, Wenxin; Lin, Xiaoxi (Lasers in surgery and medicine, 2025)
ABSTRACT Background Both nonablative fractional (NAFL) laser combined with intense pulsed light (IPL) and picosecond alexandrite laser (PSAL) with diffractive lens array (DLA) have been documented for their efficacy in facial rejuvenation. Objective To observe the safety and efficacy of PSAL‐DLA and IPL‐NAFL in the rejuvenation of Chinese individuals. Methods Each subject (n = 18) received three treatments on half of their face, with 1‐month interval between treatments. One side of the face was randomly treated with PSAL‐DLA, and the other side with IPL‐NAFL. Quantitative data of wrinkles, pores, brown spots, and red areas were calculated using the VISIA‐CR imaging system 3 months after the final treatment. Secondary outcomes included a 10‐point VAS for patient‐rated pain sensation, incidence of post‐inflammatory hyperpigmentation (PIH), erythema and edema, and overall satisfaction. Adverse events were recorded after each treatment and at each follow‐up. Results A total of 17 Chinese female patients aged 28.2 ± 4.3 years completed the study and the 3‐month follow‐up. The IPL‐NAFL side showed a statistically significant improvement in pores compared to baseline (p < 0.05); the PSAL‐DLA side showed a statistically significant improvement in brown spots compared to baseline (p < 0.01). Compared to PSAL‐DLA, the improvement in enlarged pores was better for IPL‐NAFL (81.8 ± 128.1 vs. 20.8 ± 132.4, p < 0.01). In terms of pain, IPL‐NAFL was more painful than PSAL‐DLA (6 ± 1 vs. 4 ± 1, p < 0.01), a longer recovery time for erythema and edema (5 ± 1 vs. 2 ± 1, p < 0.001), and a higher incidence of PIH (58.8% vs. 23.5%, p < 0.05). Patient satisfaction was higher for PSAL‐DLA than for IPL‐NAFL (3 ± 1 vs. 4 ± 0.5, p < 0.01). Conclusion Our study results indicated that both IPL‐NAFL and PSAL‐DLA could improve the photoaging, but within the same number of treatments, IPL‐NAFL was slightly more effective for enlarged pores than PSAL‐DLA, while PSAL‐DLA was more effective for brown spots than IPL‐NAFL. Patients were more satisfied with PSAL‐DLA, with a shorter postoperative recovery period and a lower incidence of PIH.